Запис динамічних ґраток за рахунок зміни параметра порядку світлом у кіральних нематичних рідких кристалах з домішкою барвника - Iljin, A.; Wei, D.; Bortolozzo, U.; Residori, S. (Publishing house "Academperiodika", 2019)
The dynamic grating recording in dye-doped chiral nematic liquid crystals is studied. It is shown that the mechanism responsible for the grating recording can be ascribed to a photoinduced modification of the order parameter of a liquid crystal within the range of optical intensities, for which the orientational nonlinearity remains quenched by the structural order of the chiral structure. The two-wave mixing dynamic behavior is analyzed for different intensities of the recording beams, by comparing the self-diffraction regime with the probe diffraction. This allows us to distinguish a particular mechanism of optical nonlinearity. The photo-induced modulation of the order parameter and the respective changes of medium’s refractive indices determine the relatively fast response times, local nonlinear response, and quite high diffraction efficiency within an extremely wide intensity range (more than three orders of magnitude) The chiral helical structure hinders the nematic director reorientation, prevents the appearance of surface effects, and is very favorable for the manipulation of a nonlinear polarization. Such new mechanism could also be extended to the recording of arbitrary phase profiles as requested in several applications for the manipulation of a light-beam.